Encapsulation with Natural Polymers to Improve the Properties of Biostimulants in Agriculture - David Jíménez-Arias; Sarai Morales-Sierra; Patrícia Silva; Henrique Carrêlo; Adriana Gonçalves; José Filipe Teixeira Ganança; Nuno Nunes; Carla S. S. Gouveia; Sónia Alves; João Paulo Borges; Miguel Â. A. Pinheiro de Carvalho (Plants, 2022)
Encapsulation in agriculture today is practically focused on agrochemicals such as pesticides, herbicides, fungicides, or fertilizers to enhance the protective or nutritive aspects of the entrapped active ingredients. However, one of the most promising and environmentally friendly technologies, biostimulants, is hardly explored in this field. Encapsulation of biostimulants could indeed be an excellent means of counteracting the problems posed by their nature: they are easily biodegradable, and most of them run off through the soil, losing most of the compounds, thus becoming inaccessible to plants. In this respect, encapsulation seems to be a practical and profitable way to increase the stability and durability of biostimulants under field conditions. This review paper aims to provide researchers working on plant biostimulants with a quick overview of how to get started with encapsulation. Here we describe different techniques and offer protocols and suggestions for introduction to polymer science to improve the properties of biostimulants for future agricultural applications.